2008
DOI: 10.1161/circresaha.107.168724
|View full text |Cite
|
Sign up to set email alerts
|

Negative-Feedback Loop Attenuates Hydrostatic Lung Edema via a cGMP-Dependent Regulation of Transient Receptor Potential Vanilloid 4

Abstract: Abstract-Although the formation of hydrostatic lung edema is generally attributed to imbalanced Starling forces, recent data show that lung endothelial cells respond to increased vascular pressure and may thus regulate vascular permeability and edema formation. In combining real-time optical imaging of the endothelial Ca 2ϩ concentration ([Ca 2ϩ ] i ) and NO production with filtration coefficient (K f ) measurements in the isolated perfused lung, we identified a series of endothelial responses that constitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
122
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 124 publications
(129 citation statements)
references
References 32 publications
6
122
1
Order By: Relevance
“…These findings point to an interesting possibility that PKG phosphorylates the channel at a site that is different from protein kinase C or protein kinase A phosphorylation, and results in channel inhibition. Previous studies by Yin et al17 using Fura‐2 indicated that NO‐cGMP signaling lowers TRPV4‐induced increases in global Ca 2+ levels in lung venular capillary endothelium. Whether this effect of NO is because of a direct effect on single channel function of TRPV4 channels remains unknown.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These findings point to an interesting possibility that PKG phosphorylates the channel at a site that is different from protein kinase C or protein kinase A phosphorylation, and results in channel inhibition. Previous studies by Yin et al17 using Fura‐2 indicated that NO‐cGMP signaling lowers TRPV4‐induced increases in global Ca 2+ levels in lung venular capillary endothelium. Whether this effect of NO is because of a direct effect on single channel function of TRPV4 channels remains unknown.…”
Section: Discussionmentioning
confidence: 96%
“…NO can alter the activity of several ion channels by S ‐nitrosylation or activation of guanylyl cyclase‐protein kinase G (GC‐PKG) signaling 13, 14, 15, 16, 17. In cultured cells, S ‐nitrosylation of TRPV4 channels increased the channel function,18 and activation of GC‐PKG signaling reduced the channel activity 19.…”
mentioning
confidence: 99%
“…Our experiments rule out downregulation of eNOS or lack of eNOS substrate which have been shown to underlie endothelial dysfunction in pulmonary arterial hypertension, 31,32 and consequently suggest that lung endothelial dysfunction in CHF may be attributable to impaired posttranslational regulation of eNOS. 17,22 failed to elicit a [Ca 2ϩ ] i increase in CHF lungs. TRPV4 and TRPV2 were both downregulated in CHF, seemingly supporting the notion that downregulation of these cation channels may underlie the loss of endothelial mechanosensitivity.…”
Section: Lung Endothelial Dysfunction In Chfmentioning
confidence: 93%
“…Ca 2ϩ concentration in cytosol ([Ca 2ϩ ] i ) and endosomal stores of lung endothelial cells was quantified by ratiometric imaging of fura-2 and fura-2FF, respectively. 17 The endothelial F-actin cytoskeleton was visualized by Alexa 568 phalloidin staining as described. 18 Immunofluorescence staining for ␣-smooth muscle actin in lung microvessels was performed as reported.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, TRPV4-mediated Ca 2+ influx elicited by cyclic strain triggers cytoskeletal remodeling and movement necessary for cell realignment in the vasculature [292] . TRPV4 channels are extensively expressed in alveolar septal capillaries [163,313] , where they control lung endothelial permeability and barrier integrity in response to intravascular and airway pressures [314][315][316] . More specifically, TRPV4-gated Ca 2+ entry increases vascular permeability to such an extent that barrier disruption and alveolar flooding may occur [313] .…”
Section: Trpv2mentioning
confidence: 99%